Unlocking Private Investment : A Roadmap to Achieve Côte d’Ivoire’s 42 Percent Renewable Energy Target by 2030 - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
Countries around the world are working towards a low-carbon future. Since the adoption of the Paris Agreement in December 2015, 189 countries have submitted national plans that set clear goals to increase investment in renewable energy, energy efficiency, sustainable infrastructure, climate-smart agriculture, and more. Beyond setting the stage for bottom-up action, these Nationally Determined Contributions (NDCs) also opened massive potential for investment—nearly $23 trillion according to the 2016 International Finance Corporation (IFC) Climate Investment Opportunities in Emerging Markets report. Much of this investment will need to come from the private sector. Governments— including Cote d’Ivoire—are increasingly interested in working with the private sector to unlock vital finance and develop innovative solutions. Costs for renewable energy are rapidly decreasing and in certain cases can be less expensive than generating electricity from fossil fuels. This has helped to radically change the model of energy development and access around the globe, and a larger share of the energy mix is expected to be renewable in future. In regions like Sub-Saharan Africa where there is high interest in expanding infrastructure to improve access to energy, there is an opportunity to leapfrog traditional electrification approaches and develop new models that are cleaner, more efficient, and focused on customer and business needs. Cote d’Ivoire’s commitments are ambitious. The country's NDC, released in 2016, set a target to reduce its greenhouse-gas emissions by 28 percent by 2030, including a target to generate 42 percent of electricity from renewable energy by 2030. As highlighted in the IFC Climate Investment Opportunities report, the country is focused on spurring economic growth and solidifying its role as an economic engine for West Africa. The government recognizes the key role of private sector investment in expanding renewable energy penetration. Overall, Cote d’Ivoire’s 2016-2020 National Development Program aims to attract $32 million in private investment. The main drivers of sustained growth are expected to be both public and private investments in infrastructure, opening significant opportunities for the energy and electricity sectors. The Ministry of Petroleum, Energy and Renewable Energy Development is developing the overall strategy and policy framework for including renewables into the energy mix. The Societe des Energies de Cote d’Ivoire (CI-Energies), a state-owned asset holding company, is moving this framework forward and has mapped technology-specific needs and is offering tenders to develop the projects that will contribute to NDC goals. Although Cote d’Ivoire has yet to increase its power generation capacity, it has made substantial progress in improving the existing transmission and distribution network and restoring the energy sector’s financial viability.